Socioeconomic costs and health-related quality of life in juvenile idiopathic arthritis: a cost-of-illness study in the United Kingdom. Issue 1 (December 2016) - Angelis, Aris; Kanavos, Panos; López-Bastida, Julio; Linertová, Renata; Serrano-Aguilar, Pedro
Abstract Background Juvenile idiopathic arthritis (JIA) refers to a number of rare chronic inflammatory diseases. Although JIA imposes a significant societal burden, limited data are available on the cost of JIA. The study's objective is to quantify the socioeconomic burden of JIA patients in the United Kingdom (UK), along with their health-related quality of life (HRQoL). Methods A bottom-up, cross-sectional, cost-of-illness analysis of 23 patients was carried out. To collect data on demographic characteristics, health resource utilization, informal care, productivity losses and HRQoL, questionnaires were administered to and completed by patients or their caregivers. The EuroQol five dimensions (EQ-5D) instrument was used to measure HRQoL. Results This study found that the average annual cost for a JIA patient was €31, 546, with direct health care costs equalling €14, 509 (46.0 % of total costs), direct non-health care costs amounting to €8, 323 (26.4 %) and productivity losses being €8, 715 (27.6 %). This was calculated using unit costs for 2012. The largest expenditures on average were accounted for by early retirement (27.0 %), followed by informal care (24.1 %), medications (21.1 %), outpatient and primary health care visits (13.2 %) and diagnostic tests (7.9 %). Important differences existed between JIA patients in need of caregiver assistance and those with no need (€39, 469 vs. €25, 452 respectively). Among adult JIA patients, mean EQ-5D index scores and visual analogue scale (VAS) scores were found to be 0.26 and 49.00 respectively; the same scores among caregivers were 0.66 and 67.14 respectively. Conclusion JIA poses a significant cost burden on the UK society. Over half of the total average costs (54 %) are related to non-health care and productivity losses. HRQoL of JIA patients is considerably worse than the UK general population.